Conservation of Native Wild Ivory-White Olives from the MEDES Islands Natural Reserve to Maintain Virgin Olive Oil Diversity - Anallely López-Yerena; Antònia Ninot; Julián Lozano-Castellón; Elvira Escribano-Ferrer; Agustí J. Romero-Aroca; Angjelina Belaj; Anna Vallverdú-Queralt; Rosa M. Lamuela-Raventós (MDPI AG, 2020)
Food diversity, and in particular genetic diversity, is being lost at an alarming rate. Protection of natural areas is crucial to safeguard the world's threatened species. The Medes Islands (MI), located in the northwest Mediterranean Sea, are a protected natural reserve. Wild olive trees also known as oleasters make up part of the vegetation of the Meda Gran island. Among them, in 2012, a wild albino ivory-white olive tree with fruit was identified. Fruits were collected from this tree and their seeds were first sown in a greenhouse and then planted in an orchard for purposes of ex situ preservation. Seven out of the 78 seedling trees obtained (12%) produced ivory-white fruits. In autumn 2018, fruits from these trees were sampled. Although the fruits had low oil content, virgin olive oil with unique sensory, physicochemical, and stability characteristics was produced. With respect to the polyphenols content, oleacein was the main compound identified (373.29 ± 72.02 mg/kg) and the oleocanthal was the second most abundant phenolic compound (204.84 ± 52.58 mg/kg). Regarding pigments, samples were characterized by an intense yellow color, with 12.5 ± 4.6 mg/kg of chlorophyll and 9.2 ± 3.3 mg/kg of carotenoids. Finally, oleic acid was the main fatty acid identified. This study explored the resources of the natural habitat of the MI as a means of enrichment of olive oil diversity and authenticity of this traditional Mediterranean food